Fenestrated Endovascular Aortic Aneurysm Repair (FEVAR) for Complex Thoracoabdominal and Abdominal Aortic Aneurysms: First Iranian FEVAR Series Report with Mid-Term Follow-up - Ali Mohammad Haji Zeinali; Kyomars Abbasi; Mahmmod Shirzad (Journal of Tehran University Heart Center, 2018)
Endovascular treatment of aortic diseases has improved in recent years. More complex thoracoabdominal and juxtarenal abdominal aortic aneurysms can now be treated with new stent grafts and techniques. Fenestrated endovascular aortic aneurysm repair (FEVAR) with fenestrated stent grafts was commenced in our center after hundred cases of endovascular aortic repair, and so far 4 serial complex cases deemed inoperable (2 juxtarenal abdominal aortic aneurysms, 1 thoracoabdominal aneurysm, and 1 thoracoabdominal pseudoaneurysm) have been treated with FEVAR. All these patients needed custom-made stent grafts, which were designed and implanted successfully under general anesthesia in the catheterization laboratory. They were followed up for more than 1 year, with a median follow-up period of 23.0 months. There were no major in-hospital or short-term complications. Only 1 patient had midterm unilateral iliac artery thrombosis, which was successfully managed interventionally. Computed tomography angiography at 1 year’s follow-up showed that the stent grafts were patent and their visceral branch cover stents had no endoleak.